Effect of a congested match schedule on immune-endocrine responses, technical performance and session-RPE in elite youth soccer players. Issue 24 (16th December 2016) - Moreira, Alexandre; Bradley, Paul; Carling, Christopher; Arruda, Ademir Felipe Schultz; Spigolon, Leandro M. P.; Franciscon, Clovis; Aoki, Marcelo Saldanha
ABSTRACT: This study investigated the effects of a congested match schedule (7 matches played in 7 days) on steroid hormone concentrations, mucosal immunity, session rating of perceived exertion (S-RPE) and technical performance in 16 elite youth soccer players (14.8 ± 0.4 years; 170.6 ± 9.4 cm; 64.9 ± 7 kg). No change was observed for salivary cortisol concentration across match time points ( P = 0.33; effect size [ES] = 0.13–0.48). In contrast, there was a decrease in salivary testosterone and salivary IgA (SIgA) concentrations from the 1st compared with the last time point ( P = 0.01 and 0.001, ES = 0.42 and 0.67, respectively). The SIgA concentration varied across time points ( P < 0.001) with the highest value observed at the 3rd time point (rest day) (3rd vs all time point; ES = 0.47–0.73). No changes were observed for S-RPE across time points ( P > 0.05). A higher number of tackles and interceptions were observed during the 4th match vs 1st and 7th matches ( P < 0.001; ES = 2.25 and 1.90, respectively). The present data demonstrate that accumulated fatigue related to participation in a congested match schedule might induce a decrease in testosterone concentration in youth players and negatively affect their mucosal immunity and capacity to perform certain technical actions.